Natural dyes as photo-sensitizer in solar cells - Silwal, Surendra Bikram; Adhikari, Rameshwar; Lamichhane, Prakash; Bhandari, Netra Lal (BIBECHANA, 2020)
The objective of this research is to employ the natural dyes in dye-sensitized solar cell (DSSC). On account of eco-friendly, renewable, and non-hazardous properties of natural dyes over silicon, a semiconductor, photo-sensitizer in conventional solar cells, cyclohexane extract of Terminalia alata, a natural dye, was employed as photo-sensitizer. The photoanodes ZnO and 5% Al-doped ZnO for DSSCs were developed by spray pyrolysis. The X-ray diffraction (XRD) has shown hexagonal wurtzite structure of ZnO with lattice constants a = 3.2487 Å and b = 5.1518 Å having particle size 25.85 nm for ZnO and 33.17 nm for Al-doped ZnO. The DSSC properties such as solar conversion efficiency (η), short-circuit current density (Jsc), open-circuit voltage (Voc), and fill factor (FF) were found to be 0.31%, 2.10 mA/cm2, 0.73V, and 45% for ZnO photoanode and 0.37%, 2.25mA/cm2, 0.70 V, and 52.10% for 5% Al-doped photoanode respectively. BIBECHANA 17 (2020) 27-32